2018
DOI: 10.1007/s00384-018-3136-1
|View full text |Cite
|
Sign up to set email alerts
|

Morbidity, mortality, and survival in elderly patients undergoing pulmonary metastasectomy for colorectal cancer

Abstract: Morbidity, mortality, and overall survival after PM with lymphadenectomy for elderly patients were comparable to younger patients. A disease-free interval > 36 months and anatomic lung resections might be associated with prolonged survival. However, elderly patients should also be evaluated for a curative treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
1
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 24 publications
2
18
1
4
Order By: Relevance
“…Specifically, they observed that patients with no lymph node involvement survived twice as long as those with lymph node involvement (median survival 94 months versus 42 months in patients with positive lymph node involvement). On the other hand, we have also found studies that did not find significant differences, such as those of Sponholz et al (15) and Kumar et al (16). Sponholz studied 54 over-70-year-old who underwent surgery in Germany, and the only factors that reached significance were disease-free interval and anatomic resection (15), while Kumar analysed 71 patients who underwent surgery in India, and concluded that in their series, the only variables with an impact on survival were a history of extra-pulmonary metastasis and local lymph node invasion at the time of the primary tumour surgery (16).…”
Section: Impact Of Thoracic Lymph Node Involvement On Survival Following Lung Metastasectomysupporting
confidence: 58%
See 1 more Smart Citation
“…Specifically, they observed that patients with no lymph node involvement survived twice as long as those with lymph node involvement (median survival 94 months versus 42 months in patients with positive lymph node involvement). On the other hand, we have also found studies that did not find significant differences, such as those of Sponholz et al (15) and Kumar et al (16). Sponholz studied 54 over-70-year-old who underwent surgery in Germany, and the only factors that reached significance were disease-free interval and anatomic resection (15), while Kumar analysed 71 patients who underwent surgery in India, and concluded that in their series, the only variables with an impact on survival were a history of extra-pulmonary metastasis and local lymph node invasion at the time of the primary tumour surgery (16).…”
Section: Impact Of Thoracic Lymph Node Involvement On Survival Following Lung Metastasectomysupporting
confidence: 58%
“…On the other hand, we have also found studies that did not find significant differences, such as those of Sponholz et al (15) and Kumar et al (16). Sponholz studied 54 over-70-year-old who underwent surgery in Germany, and the only factors that reached significance were disease-free interval and anatomic resection (15), while Kumar analysed 71 patients who underwent surgery in India, and concluded that in their series, the only variables with an impact on survival were a history of extra-pulmonary metastasis and local lymph node invasion at the time of the primary tumour surgery (16). Taking broader view, we found research analysing metastases from kidney cancer (17), which observed a clear tendency towards a poorer survival rates with increasing lymph node stage, with mean survival times of 71.9, 50.7 and 36 months in patients with N0, N1 and N2 disease, respectively (17).…”
Section: Impact Of Thoracic Lymph Node Involvement On Survival Following Lung Metastasectomysupporting
confidence: 58%
“…In metastases resections for colorectal metastases, minor morbidity, major morbidity, and mortality were 17, 5.8, and 0%, respectively. 9 Other authors demonstrated a comparable morbidity for metastatic surgery. A video-assisted surgery was associated with lower morbidity.…”
Section: Discussionmentioning
confidence: 92%
“…Other prerequisites for an operation are low perioperative and postoperative morbidity and mortality rates, which we have already demonstrated for pulmonary metastasectomy with complete systematic lymph node dissection in previous studies. 18,32 However, because of their proximity to the trachea, the esophagus, the thoracic duct, the superior vena cava, and the recurrent laryngeal nerve, ITLNM resection might be associated with a high risk of morbidity, and resection can be challenging. However, with a morbidity rate of 13% and without any mortality, we have now demonstrated that the resection of these metastases is feasible with good perioperative and postoperative results.…”
Section: Commentmentioning
confidence: 99%